PENAFSIRAN AYAT-AYAT AMTHĀL DALAM KITAB TAFSIR AL-IBRĪZ KARYA KH. BISRI MUSTOFA - Muzayyan, Ahmad Labiq (QOF, 2020)
Amthāl is the uslūb al-Qur’ān expressing various explanations and aspects of the Qur'an miracle. Understanding and interpreting amthāl can be influenced by current development and certain society condition. To find out the influence of that on the understanding of amthāl in the Qur'an, research is focused on KH. Bisri Mustofa interpretation on the amthāl verses in the al-Ibrīz because it has a context in the process of socializing the Qur'an oriented in the pesantren-coastel society. Based on the research using mauḍū’ī (thematic) method, there are two important poins. First, Kiai Bisri and most commentators only pay attention to amthāl muṣarraḥah. However, he gives more attention to the divinity aspects and sometimes gives his own parables in familiar terms for the community. Secondly, Kiai Bisri interpretation is relevant with the problems of society today about human relations with god and the consequences of all deeds in the world.